COVID-19 and its manifestations in the oral cavity A systematic review - Cuevas Gonzalez, Maria Veronica; Espinosa Cristobal, Leon Francisco; Donohue-Cornejo, Alejandro; Tovar Carrillo, Karla Lizette; Saucedo Acuña, Rosa Alicia; Garcia-Calderón, Alma Graciela; Guzmán-Gastélum, Dalia Abril; Cuevas-González, Juan Carlos (2021)
Background: SARS-CoV-2 is the virus responsible for coronavirus disease-19 (COVID-19) disease, which has been shown to trigger multiple affectations. One of the first tissue areas to come into contact with the virus is the oral cavity, which develops various alterations. Hence, the objective of this systematic review was to identify the main signs and symptoms of this disease in the oral cavity, and the following research question was established: What are the main oral signs and symptoms in COVID-19-positive persons? Methods: The electronic databases of PUBMED, SCOPUS, and SCIENCE DIRECT were analyzed, the keywords “ORAL DISEASES,” “ORAL MANIFESTACTIONS,” and “COVID-19” were used taking into account the following inclusion criteria: studies whose main objective was oral manifestations secondary to the confirmation of COVID-19, plus clinical cases, case series, and retrospective or prospective studies. For the assessment of the risk of bias the JBI Critical Appraisal Checklist for Case Series tool was used. Results: A total of 18 studies were included, the most common initial signs/symptoms after contagion of SARS-CoV-2 were dysgeusia, dry mouth, and burning mouth, and the main signs/symptoms were the presence of ulcerative lesions, dysgeusia, and Candida albicans infections. Conclusions: It is very important to detect any alteration in the mucosa in patients with COVID-19 and to provide assertive treatment to avoid complications, and try to maintain adequate oral hygiene throughout the course of the disease to avoid the colonization of opportunistic microorganisms and to avoid complications both orally and systemically. Abbreviation: ACE2 = receptor angiotensin-converting enzyme 2.